LGBT dalam Perspektif Alkitab Sebagai Landasan Membentuk Paradigma Etika Kristen terhadap Pergaulan Orang Percaya - Christian Bayu Prakoso; Yonatan Alex Arifianto; Aji Suseno (Jurnal Teologi (JUTEOLOG), 2020)
The LGBT phenomenon is increasingly spreading among the wider community. The existence of social media allows everyone to access information quickly and easily. The church, which is directly related to the social environment, also takes an attitude towards this phenomenon. There are many different attitudes raised by a particular church or denomination. Therefore, this paper aims to find out carefully about the Bible's view of LGBT as the basis for forming a Christian ethical paradigm. The result of this research is that LGBT acts are a sin in God’s view. God does not want people to commit LGBT acts. But on the other hand, as an agent that embodies the application of God's love, the church is required to continue to follow LGBT people and provide faith formation and preventive measures to the congregation.